2019
DOI: 10.3390/su11082451
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Informatization and Technical Efficiency in Maize Production in Zambia

Abstract: The cropland productivity gap between Africa and the rest of the world is widening. Fortunately, increasing farmers’ access to useful agricultural information reduces the costs of searching for information, thereby leading to higher agricultural productivity and sustainability. This study investigates the association between the adoption of mobile phones to collect agricultural information and farmers’ technical efficiency (TE) in Zambia. Different from previous studies, we focus on the actual use of mobile ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 64 publications
8
55
0
Order By: Relevance
“…For instance, in a recent article by Candemir, Özcan, Güneş and Deliktaş [14], technical efficiency estimations are conducted without addressing endogeneity and other biases stemming from unobserved variables. This according to Bravo-Ureta, et al [31] does not give robust estimates, as estimates could be exaggerated as found by Mwalupaso, et al [32]. In another study, Guney [9] presents a discourse on hazelnut production without indicating the productivity levels.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…For instance, in a recent article by Candemir, Özcan, Güneş and Deliktaş [14], technical efficiency estimations are conducted without addressing endogeneity and other biases stemming from unobserved variables. This according to Bravo-Ureta, et al [31] does not give robust estimates, as estimates could be exaggerated as found by Mwalupaso, et al [32]. In another study, Guney [9] presents a discourse on hazelnut production without indicating the productivity levels.…”
Section: Introductionmentioning
confidence: 89%
“…Considering that hazelnut production takes place in an orchard environment, farmers' understanding of how to produce is more important than attainment of general education [54]. An insignificant and positive sign on education was also found by Mwalupaso, Wang, Rahman, Alavo and Tian [32] and Bozoglu and Ceyhan [67]. Regarding NGO intervention being insignificant, the translog production function (another specification applied as a robust check) discloses consistent results to those in Table 4, implying that no bias is introduced on account of the interaction of the classical inputs.…”
Section: Impact Of Ngo Intervention On Technical Efficiencymentioning
confidence: 98%
“…Otherwise, there might be some loss of technical efficiency. Much literature pays attention to the determinants of technical efficiency in agriculture [24,[26][27][28], among which were a growing number of studies focusing on the aging of agricultural labor force [2,9].…”
Section: Theoretical Analysismentioning
confidence: 99%
“…The existing studies have categorized them into natural factors, socioeconomic factors, and resource endowments [7,8]. Therefore, the exploration of the relationship between the production efficiency and its influencing factors can be conducive to maintain and improve the overall efficiency of forest production and management.Production efficiency is usually used to present the performance of a production unit [9]. It is commonly calculated by using the ratio of the actual output to the maximum output conditional on a given input, or the ratio of the minimum input to the actual input conditional on a given output [10,11].…”
mentioning
confidence: 99%
“…Production efficiency is usually used to present the performance of a production unit [9]. It is commonly calculated by using the ratio of the actual output to the maximum output conditional on a given input, or the ratio of the minimum input to the actual input conditional on a given output [10,11].…”
mentioning
confidence: 99%